Educational orientation: How to achieve a successful process? - Guzmán Zegarra, Natalia (2019)
The objective of the present article is to make a theoretical review of the educational orientation: the evolution of its definitions, its fields of action, how it is conducted in our times and what its relevance is. This bibliographic review aims to gather the main theoretical axes of educational orientation, in order to know the impact of this variable on people’s lives.